A Case with Bladder Exstrophy and Unbalanced X Chromosome Rearrangement - Soderhall, Cilla; Lundin, Johanna; Lagerstedt-Robinson, Kristina; Grigelioniene, Giedre; Lackgren, Goran; Kockum, Christina Clementson; Nordenskjold, Agneta (European Journal of Pediatric Surgery, 2014)
Introduction Bladder exstrophy is a rare congenital malformation of the bladder and is believed to be a complex disorder with genetic and environmental background. We describe a young adult female with an isolated bladder exstrophy and with an X chromosome aberration.Patients and Methods Karyotyping identified an X chromosome rearrangement that was further characterized with array comparative genomic hybridization (CGH) and confirmed by multiplex ligation–dependent probe amplification and fluorescence in situ hybridization (FISH) analysis.Results The identified X chromosome rearrangement in our index patient consists of a gain of chromosomal material in region Xq26.3- > qter and loss in region Xp22.12- > pter. This aberration was also carried by her mother and sister, none with bladder exstrophy. All three have a disproportionate short stature, as expected due to the deletion of one of the copies of the SHOX gene on Xp22.3. X-inactivation studies revealed a complete skewed inactivation pattern in carriers. Crossover events in the maternal germline furthermore resulted in different genetic material on the rearranged X chromosome between the index patient and her sister.Conclusion Our findings suggest an X-linked genetic risk factor for bladder exstrophy.
Keywords: array-CGH; bladder exstrophy; MID1; SHOX; X chromosome rearrangement